The Shock of the Anthropocene - Christophe Bonneuil; Jean-Baptiste Fressoz (Geografares, 2023)
Translation, from the original in French, of the preface and chapters 1 and 2 of the book by Christophe Bonneuil and Jean-Baptiste Fressoz. L’événement Anthropocene. La terre, l’histoire et nous. Paris : Seuil, 2016 [2013].